Fêtes et processions de Maaloula : une mise en scène des identités dans l’espace d’un village chrétien - Sylvia Chiffoleau (Revue des Mondes Musulmans et de la Méditerranée)
The Ba‘th regime has appropriated most festive events in Syria. A few popular festivals continue, however, and reveal through their exceptional nature a variety of generally discouraged or banned identities popular among Syrians. Such is the case of the Christian village of Maaloula where, at the end of the summer, the Catholic and Orthodox Churches jointly celebrate a Feast of the Cross, before honouring their respective patron saints. A mixture of identities dominated by a regionally differentiated and doctrinally diverse Christianity are enacted in the village setting. The enactment and resulting identities, marked by strong Syrian influence, emerge as a process of renewal and modernization leading to social change, global integration and to religious and secular independence. The festivals of Maaloula assume a utopian dimension and suggest that another world is possible, a world based on freedom.